Design and development of innovative non active medical devices: Clean air suits - Ribeiro, Patricia (2014)
Design fitting and comfort are an important subject to consider when we need clothes for protective and individual equipment. Construction of protective equipment requires ergonomics, fabrics and performance requirements studies. This paper is about the construction of clean air suits (CAS) for use in the operating room. This suits were developed to minimize the contamination in operating rooms. It’s important to develop clothing with good protective barriers, however attention must be given to comfort to obtain a suit that answers effectively for both protection and comfort requirements. Our study consists in selecting the best fabrics, woven and non-woven, that could manage protective and comfort requirements. We’re developing several designs, in order to foreseen the best design approach to a clean air suit. Normally these kind of suits need to be closed at the bottom legs and sleeves in order to minimize skin particles dispersion.